The relation between photography and painting for Francis Bacon according to Deleuze (in The Logic of Sensation) - Heusghem, Corentin (Hybris, 2021)
The aim of this article is to present a concise summary and review about the theses of Deleuze on the relations between painting and photography but also about his account of Bacon through the prism of this question in his book Francis Bacon : Logique de la sensation. This article could only be seen as an introduction and perhaps an invitation to read deeper studies about the important and numerous links between Deleuze's philosophy and art.